2012
DOI: 10.1177/0010836712462781
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and trust: Prüm and the institutional design of EU internal security

Abstract: One recent but major policy occurrence in Justice and Home Affairs -the Treaty of Prüm (2005) -has developed within the framework of differentiated integration, thus reopening the debate over the impact of flexibility on EU integration, what causes it, and whether it should be sought by Member States at all. Whatever the consensus, the debate itself demonstrates that the very idea of differentiated integration deserves a renewed attention today ultimately because it affects, in one way or another, the performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…Empirical studies of differentiated integration also became more prominent from 2005 onwards. These include a special issue of the Journal of European Integration on Euro‐outsiders (Miles, ) as well as studies on the impact of non‐eurozone membership (for example, Marcussen, ), opt‐outs in Justice and Home Affairs (Adler‐Nissen, , , ; Balzacq and Hadfield, ), the Single Market (Howarth and Sadeh, ) and the Common Foreign and Security Policy (for example, Lavenex, ). Two influential EU‐funded research networks (CONNEX and EUROGOV) concluded that even the study of European integration was unable to integrate (Kohler‐Koch and Larat, ) and that the EU was characterized by multiple – and thus differentiated – ‘modes’ of governance (see Héritier and Rhodes, ).…”
Section: Differentiated Integration As a Field Of Study: A Chronolmentioning
confidence: 99%
“…Empirical studies of differentiated integration also became more prominent from 2005 onwards. These include a special issue of the Journal of European Integration on Euro‐outsiders (Miles, ) as well as studies on the impact of non‐eurozone membership (for example, Marcussen, ), opt‐outs in Justice and Home Affairs (Adler‐Nissen, , , ; Balzacq and Hadfield, ), the Single Market (Howarth and Sadeh, ) and the Common Foreign and Security Policy (for example, Lavenex, ). Two influential EU‐funded research networks (CONNEX and EUROGOV) concluded that even the study of European integration was unable to integrate (Kohler‐Koch and Larat, ) and that the EU was characterized by multiple – and thus differentiated – ‘modes’ of governance (see Héritier and Rhodes, ).…”
Section: Differentiated Integration As a Field Of Study: A Chronolmentioning
confidence: 99%
“…Instead, rapid decisionmaking was preferred to intense negotiations with national parliaments and EU institutions (for a criticism, see Walsch [2008]). Since Prüm was a counterproposal to the Commission's principle of availability (Balzacq and Hadfield 2012;Kietz and Maurer, 2006), outside cooperation allowed the signatories to realize their own preferences rather than seek compromise with other member states under the control of the EU bodies (Kietz and Maurer 2006).…”
Section: The Prüm Conventionmentioning
confidence: 99%
“…One topic of debate has been the differentiations in power, interests and trust among the Member States and how these aspects could bring implications in the Prüm system, as well as the consequences for the wider processes of European integration [14], [17]. Dimensions related to privacy and data protection issues raised by Prüm have also been the subject of analysis, mainly referring to the implementation of common minimal standards of data protection under Prüm and the diversity of legal frameworks in EU Member States [20], [21], [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature in the field of social sciences has focused on the institutional and political consequences of the implementation and development of the Prüm system and the associated exchange of forensic information among EU Member States [13] , [14] , [15] , [16] , [17] , [18] , [19] . One topic of debate has been the differentiations in power, interests and trust among the Member States and how these aspects could bring implications in the Prüm system, as well as the consequences for the wider processes of European integration [14] , [17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation